2020
DOI: 10.3390/ijerph17113811
|View full text |Cite
|
Sign up to set email alerts
|

Emotional-Behavioral Functioning, Maternal Psychopathologic Risk and Quality of Mother–Child Feeding Interactions in Children with Avoidant/Restrictive Food Intake Disorder

Abstract: The literature on food intake disorder (ARFID) in early childhood has evidenced psychopathologic difficulties in both children and their mothers and a poor quality of feeding interactions. Only a few studies have focused on three different ARFID subtypes: irritable/impulsive (I/I), sensory food aversions (SFA) and post traumatic feeding disorder (PTFD). The aim of this study was to explore possible differences between the three groups in children’s emotional-behavioral functioning, maternal psychopathologic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 68 publications
(88 reference statements)
5
18
0
1
Order By: Relevance
“…This study suggests that even a child exposed to an early food-related trauma may be at higher risk to develop dysregulation problems. Moreover, our findings are in accordance with previous studies that have shown the highest psychopathological risk in children with PTFD and among their mothers compared to other ARFID diagnosis [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study suggests that even a child exposed to an early food-related trauma may be at higher risk to develop dysregulation problems. Moreover, our findings are in accordance with previous studies that have shown the highest psychopathological risk in children with PTFD and among their mothers compared to other ARFID diagnosis [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, these children reported the lowest dysregulation problems compared to other clinical groups and, in turn, their mothers’ showed the lowest psychopathological risk than mothers of other ARFID groups. These results are in line with the study by Lucarelli and colleagues [ 28 ] and Cerniglia and colleagues [ 31 ] that have evidenced lower psychopathological problems in children with SFA and among their mothers, compared to other ARFID subtypes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations